Multivariate Forecasting of Electricity Consumption for Sustainable Energy Planning - Hakim, Lukmanul; Septama, Hery Dian (International Journal of Sustainable Energy Planning and Management, 2025)
Forecasting accurate consumption of electricity is crucial for energy security of a rapidly grown region. Prior study proves that there is a positive relationship between electricity consumption, population and economic growth. Nevertheless, only a few have applied the multivariate model within a regional context for the long-term electricity forecasting. This study tries to bridge the gap in forecast reliability by using machine learning to support regional sustainable energy planning in the Lampung Province. The methodology includes data preprocessing, integration, and cleaning, and model training and validation using time-series data. The Vector Autoregressive (VAR) was employed to predict electricity consumption from 2024 to 2030 based on historical data from 2010 to 2023. The model demonstrated a robust predictive performance, with a low MAPE of 0.57%, RMSE of 37.74, and a high R² value of 0.998. This instills confidence in the findings of the research and the future use of the VAR for electricity forecasting. The model suggests that the trend of energy consumption in Lampung Province is continuously increasing. The study also stresses the need for renewables to meet future electricity needs, ensuring energy infrastructure tackles socio-economic growth and the energy transition agenda with regard to the development of Lampung Province.